Determinan Kinerja Sosial (Sosial Performance) Lembaga Keuangan Mikro : Studi pada Koperasi Simpan Pinjam di Kecamatan Kota Baru - Yuliana Sitorus (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
Besides having a financial mission, microfinance institutions also have a social mission that is measured through social performance. Social performance is the cooperative's ability to serve clients / customers who are micro, small and poor businesses as measured by the depth and width of the main services provided by microfinance institutions. This study aims to determine the determinants of social performance consisting of AGE, ROA, number of customers, banking intermediation, number of employees and cost of credit in savings and loan cooperatives in Kota Baru, both simultaneously and partially. The objects of this research are 6 savings and loan cooperatives in Kota Baru. The analytical method used is descriptive quantitative method with verification test. The analysis tool used is Multiple Linear Regression analysis. From the research results using the F test shows that the independent variables AGE, ROA, number of customers, banking intermediation, number of employees and cost of credit simultaneously have a significant effect on the social performance of financial institutions. Partially with the t test that the AGE variable has a significant effect on social performance, the ROA variable does not have a significant effect on social performance, the Customer variable has no significant effect on social performance, the Banking Intermediation variable does not have a significant effect on social performance, the Employee variable has a significant effect on performance. social, and the Cost of Credit variable does not have a significant effect on social performance.